2003
DOI: 10.1080/1042517021000050633
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 148 kb of Genomic DNA of Tetraodon nigroviridis Covering an Amylase Gene Family*

Abstract: We have sequenced and analysed a 148 kb genomic region of Tetraodon nigroviridis, a teleost fish with a compact genome. Several genes were identified by comparison with genomic or transcript sequences of other species, informatic prediction and screening of a cDNA library. As expected for a compact genome, sizes of the identified genes and introns are very small, and intergenic distances are short. Among identified genes, three code for amylases. As in mammals, these genes are linked, but they are found in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Further cloning of alleles indicated that alignment of sequences of each amylase locus were not possible (JL Rolland and B Guinand, unpubl. results), indicating that we probably amplified two different genes of the multigenic α-amylase gene family (Bouneau et al 2003). A new set of primers was defined for the metallothionein (MT) locus.…”
Section: Genetic Analysesmentioning
confidence: 99%
“…Further cloning of alleles indicated that alignment of sequences of each amylase locus were not possible (JL Rolland and B Guinand, unpubl. results), indicating that we probably amplified two different genes of the multigenic α-amylase gene family (Bouneau et al 2003). A new set of primers was defined for the metallothionein (MT) locus.…”
Section: Genetic Analysesmentioning
confidence: 99%
“…This included the intron of the metallothionein gene, and the third intron of pancreatic α-amylase genes. Two amylase loci are co-amplified with the same set of primers, as such loci belong to a multigenic family (Bouneau et al 2003). Further cloning of alleles indicated that sequences of each amylase locus were clearly different and impossible to align (JL Rolland and B Guinand, unpubl.…”
Section: Genetic Analysesmentioning
confidence: 99%
“…Both smooth pufferfish species have a very compact genome (8-9 times smaller than the human genome with a similar gene number) characterized by very small intron and intergenic regions, a feature which becomes evident after detailed analysis of completely sequenced regions (see for instance Gellner and Brenner, 1999;Bouneau et al, 2003b). Because of their high percentage of coding sequences (around one third of the genome), short introns (highly biased towards the range of 60-120 bp) and short intergenic regions (generally a few kilobases), these fishes are therefore models of choice for vertebrate genomes sequencing projects.…”
mentioning
confidence: 99%